Biofilm containing the Thymus serpyllum essential oil for rice and cherry tomato conservation - Roselló, Josefa; Llorens-Molina, Juan Antonio; Larran, Silvina; Sempere-Ferre, Francisca; Santamarina, M. Pilar (Frontiers in Plant Science, 2024)
Introduction. Fungal pathogens cause major yield losses in agriculture and reduce food quality and production worldwide. Purpose. To evaluate new safer alternatives to chemicals for disease management and preserve the shelf life of food, this research was conducted to: determine the chemical composition of the essential oils (EOs) of Thymus serpyllum and Thymus piperella chemotypes 1 and 2; investigate the antifungal potential of EOs in vitro against: Alternaria alternata, Bipolaris spicifera, Curvularia hawaiiensis, Fusarium oxysporum f. sp. lycopersici, Penicillium italicum, Botryotinia fuckeliana; evaluate a natural T. serpyllum extract biofilm to conserve rice grain and cherry tomatoes. Method. EOs were analyzed by GC-MS+GC-FID. EOs' antifungal activity was evaluated by dissolving Thymus extracts in PDA. Petri dishes were inoculated with disks of each fungus and incubated at 25ºC for 7 days. Results. The T. serpyllum EO displayed the best Mycelial Growth Inhibition. The antifungal effect of the T. serpyllum EO biofilm was evaluated on rice caryopsis. Disinfected grains were dipped in a conidial suspension of each fungus and sprayed with EO (300 and 600 μg/mL) prepared in Tween 20. Grains were stored. The percentage of infected grains was recorded for 30 days. The T. serpyllum EO effect on cherry tomato conservation was evaluated in vivo. Wounded fruit were immersed in the T. serpyllum EO (300 and 400 μg/mL) and inoculated with Fusarium oxysporum f. sp. lycopersici. Fruit were evaluated for 7 and 14 days. Chemical profiles thymol/carvacrol for T. serpyllum, carvacrol for T. piperella Tp1 and thymol for T. piperella Tp2 were defined. The three evaluated EOs reduced all the studied phytopathogens' fungal growth. The T. serpyllum biofilm was effective with rice storage and against Fusarium oxysporum f. sp. lycopersici for extending the shelf life of tomatoes in warehouses and storing postharvest cherry tomatoes. Conclusion. We suggest applying these EOs as biofilms for safe food conservation to replace synthetic products.